Parental Involvement in Academic Activities of Children in Tea Communities of Assam - Gogoi, Poppy; Borah, Tulika; Gogoi, Sampreety (International Journal of Bio-resource and Stress Management, 2020)
In today’s modern world, every parent wants their children to get better education. They try to involve in children’s education so that their children can have bright future and achieve good status in the society in their later life. The present study was an attempt to assess parental involvement in academic activities of their children. The involvement of parents of tea communities was assessed in four different aspects viz. Involvement of parents in school related activities, involvement of parents in home based academic activities, academic expectation and aspiration of parents and intergenerational influence on academic socialization of children. The sample consisted of 100 parents who had children studying in either lower primary or secondary school standards. From the total 100 samples, 50 respondent having children of lower primary class and 50 respondents having children of secondary standard were selected randomly. Samples were selected on the basis of stratified random sampling from the tea gardens of Jorhat district of Assam. An interview schedule was used for data collection. The results revealed that there is no difference in regards to parental involvement in school based academic of children during lower primary and secondary school standards. Also the difference was not found in case of intergenerational influences on academicsocialization of children. Differences were found in parental involvement during lower primary and secondary school standards in the aspects of involvement in home based academic activities of children and academic aspiration and expectation of parents.